Inventarisasi Jenis Paku-pakuan (Pteridophyta) Terestrial di Hutan Dusun Tauk Kecamatan Air Besar Kabupaten Landak - Irwan Lovadi, Julia Betty, Riza Linda (Jurnal Protobiont, 2015)
Ferns (Pteridophytes) are one of the sources of germ plasm that play an important role in forest ecosystem and in human’s life as well. However, due to forest conversion, ferns gradually decrease in number especially the terrestrial species. This study aims to identify all terrestrial ferns found in the forest area of Tauk Village, Air Besar District, Landak Regency. The study applied Cruise Method and lasted for four months period of time, started from March to June 2014. The findings from the inventory, there are 18 species of terrestrial ferns found in the area and identified as members of class Polypodiopsida and 13 families of ferns. Most of the species of ferns found in the area come from the family of Lygodiaceae, whereas the species with the least number come from the families of Aspleniaceae, Gleicheniacea, Nephrolepidaceae, Thelypteridaceae, Lindsaeaceae, Tectariaceae, Davalliaceae, Lycopodiaceae, and Dennstaedtiaceae.